2021
DOI: 10.1186/s12879-021-06408-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical features and outcome of children with hemophagocytic lymphohistiocytosis (HLH) secondary to visceral leishmaniasis and primary HLH: a single-center study

Abstract: Background Hemophagocytic lymphohistiocytosis (HLH) is a syndrome of excessive inflammation. We aimed to describe the clinical and laboratory findings of HLH patients secondary to Visceral leishmaniasis (VL) and their treatment outcome during a 4-year follow-up period compared to primary HLH. Method Forty children with primary HLH confirmed by genetic study and 20 children with HLH secondary to VL confirmed by a blood or bone marrow polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…Several studies ( 131 , 132 , 134 , 206 ) have reported complete response of Leishmania-associated HLH to amphotericin B therapy +/- steroids, with an excellent prognosis [3 year overall survival rate 24% in pHLH vs. 100% in visceral leishmaniasis-associated HLH; P<0.001; 2021 Iranian cohort of 60 children ( 133 )]. A Chinese retrospective study ( 135 ) reported good results with antiparasitic therapy associated with chemotherapy according to the HLH94 protocol in patients with visceral leishmaniosis-HLH; however, the cohort includes children and adults and it is impossible to discriminate whether treatment intensification depends on age.…”
Section: Treatmentmentioning
confidence: 99%
“…Several studies ( 131 , 132 , 134 , 206 ) have reported complete response of Leishmania-associated HLH to amphotericin B therapy +/- steroids, with an excellent prognosis [3 year overall survival rate 24% in pHLH vs. 100% in visceral leishmaniasis-associated HLH; P<0.001; 2021 Iranian cohort of 60 children ( 133 )]. A Chinese retrospective study ( 135 ) reported good results with antiparasitic therapy associated with chemotherapy according to the HLH94 protocol in patients with visceral leishmaniosis-HLH; however, the cohort includes children and adults and it is impossible to discriminate whether treatment intensification depends on age.…”
Section: Treatmentmentioning
confidence: 99%
“…Dentre as parasitoses, a Leishmaniose (Leishmania spp.) é um dos principais desencadeantes (MOTTAGHIPISHEH et al, 2021).…”
Section: Classificação Da Lhhunclassified
“…Em relação à LHH secundária à LV, o tratamento da causa-base com as drogas de escolha pode promover a remissão completa da doença de forma eficaz e segura (SCALZONE et al, 2016;MCCLAIN, 2020;MOTTAGHIPISHEH et al, 2021).…”
Section: Introductionunclassified
“…Lately, a new analytical score, the H-score, has been used for diagnosis. The Hscore significantly correlates with the HLH-2004 criteria, allowing for an effectual estimation of an individual's risk of having HLH [6][7][8]. In centers where genetic testing is not obtainable, the H-score is a IBM SPSS Statistics for Windows, version 25.0 (released 2017, IBM Corp., Armonk, NY) was used for statistical analysis, and t-test and chi-square tests were used for comparison between continuous and categorical variables.…”
Section: Introductionmentioning
confidence: 99%